Lame yarn and woven or knitted fabric including the same
The lame yarn with specific width and strength parameters, combined with thermoplastic synthetic fibers and titanium oxide, addresses the issues of high-definition appearance, flexibility, and soft feel in conventional lame yarns, resulting in a fabric with a fine and elegant shine.
Patent Information
- Application Number
- JP2023093686
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-07
- Publication Date
- 2024-12-19
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Conventional lame yarns struggle to achieve a high-definition appearance, flexibility, and soft feel due to the width of the glossy yarn affecting strength and the proportion of other yarns, leading to decreased decorative properties.
A lame yarn with a metallic luster yarn width of 50 μm to 130 μm, filament strength of 5.5 cN/dtex or more, total fineness of 10 dtex to 50 dtex, and a ratio of (L-D)/L of 0.70 or less, where L is the width of the metallic luster yarn and D is the filament diameter, combined with a thermoplastic synthetic fiber and optional titanium oxide for improved appearance and feel.
The solution results in a lame yarn and fabric with a high-definition appearance, soft surface touch, and reduced skin irritation, achieving a fine and elegant shine with enhanced flexibility and comfort.
Smart Images

Figure 2024175736000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a lame yarn and a woven or knitted fabric containing the same. [Background technology]
[0002] Traditionally, gold and silver threads with a metallic sheen have been widely used in women's fashion for their luxury and dazzling appearance, in printed and plain knitted fabrics, etc. They are also widely used in interior textile products such as curtains as gorgeous lamé threads.
[0003] For example, there has been proposed a lamé yarn that includes a slit glossy yarn obtained by micro-slitting a metal-deposited film and another yarn (see, for example, Patent Documents 1 and 2).
[0004] Furthermore, in order to improve the flexibility of woven and knitted fabrics using lame yarn, a composite gold and silver yarn has been proposed in which the film is randomly twisted in the longitudinal direction of the film and has a converging portion intertwined with the single filament yarn, in a composite gold and silver yarn core yarn consisting of a gold and silver yarn film and a filament (see, for example, Patent Document 3).
[0005] Furthermore, in order to improve the feel of fabrics using lame yarn, a spun twisted yarn has been proposed, which is characterized in that a metallic luster yarn obtained by slitting a laminate consisting of a base material and a metal thin film layer is used as the core yarn and a group of short fibers is used as the sheath yarn (see, for example, Patent Document 4). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 6400868 [Patent Document 2] JP 2012-207343 A [Patent Document 3] Japanese Patent Application Publication No. 11-217738 [Patent Document 4] JP 2000-54234 A Summary of the Invention [Problem to be solved by the invention]
[0007] Generally, as described above, the purpose of lame thread is to add decorativeness with an emphasis on appearance, so a certain width is required for the glossy thread using the film. For example, Patent Document 1 describes that the width of the slit lame thread obtained by micro-slitting a metal deposition film formed by laminating a metal deposition layer and a metal deposition protective layer on one side of a base film is preferably 0.15 mm or more. However, if the width is wide, a high-definition appearance cannot be obtained. In addition, in Patent Document 1, the slit lame thread and other threads are twisted together, but the other threads need to be thicker for strength as the width of the lame thread becomes narrower, which is also a reason why it is difficult to obtain a high-definition appearance. In addition, when the width of the metallic glossy thread is wide or the other threads are thick, the flexibility and feel are also poor.
[0008] On the other hand, the composite gold and silver yarn described in Patent Document 3 is said to have excellent flexibility due to a unique structure in which the film is randomly twisted in the longitudinal direction. However, in addition to being limited to a unique structure in order to obtain flexibility, the glossy yarn is wide and the fineness of the composite filaments is also large, so it was not possible to obtain a highly detailed appearance.
[0009] In addition, the technology described in Patent Document 4 improves the feel by using spinning twisted yarn, but is limited to the same unique structure as above, and does not allow for a high-definition appearance or excellent flexibility.
[0010] The inventors have investigated the reasons why a high-definition appearance is not obtained, and have found that in conventional lamé yarns, narrowing the width of the glossy yarn reduces the strength, and the other yarns must be made thicker, and that such a configuration relatively increases the ratio of the other yarns in the lamé yarn and decreases the ratio of the glossy yarn, thereby reducing the decorativeness of the lamé yarn. In other words, they have found a problem that conventional lamé yarns cannot achieve a high-definition appearance or texture such as flexibility and feel.
[0011] An object of the present invention is to provide a lamé yarn having a highly detailed appearance with precise detail and excellent softness and feel, and a woven or knitted fabric containing the same. [Means for solving the problem]
[0012] In order to solve the above problems, the present invention has the following configuration. (1) A lame yarn comprising a metallic luster yarn and a filament, wherein the width L of the metallic luster yarn is 50 μm or more and 130 μm or less, the strength of the filament is 5.5 cN / dtex or more, the total fineness of the lame yarn is 10 dtex or more and 50 dtex or less, and the ratio ((LD) / L) of the difference (LD) between the width L of the metallic luster yarn and the diameter D of the filament to the width L of the metallic luster yarn is 0.70 or less. (2) The lame yarn described in (1) above, wherein the filament is a thermoplastic synthetic fiber. (3) The lame yarn according to (1) or (2) above, wherein the filament has a modified cross-sectional shape. (4) The lame yarn according to any one of (1) to (3) above, wherein the filaments contain titanium oxide. (5) The lame yarn described in (4) above, wherein the concentration of the titanium oxide is 0.1% by mass or more and 15.0% by mass or less with respect to the filament. (6) A woven or knitted fabric comprising the lame yarn according to any one of (1) to (5) above. Effect of the Invention
[0013] According to the present invention, it is possible to obtain a lame yarn having a high-definition appearance and a soft surface touch that is soft and reduces irritation to the skin, and a woven or knitted fabric containing the same. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a schematic diagram showing one example of an embodiment of the lamé yarn of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The lame thread in the present invention refers to a thread containing a metallic luster thread and a filament. An example of a metallic luster thread is a thread obtained by coloring a film having a metallic luster by vapor deposition of a metal as necessary and cutting the film into a slit shape. However, in the present invention, as long as the thread has a metallic luster, it does not necessarily have to contain a metal. For example, the thread may be obtained by slitting a film having a metallic luster by interference coloring or the like. In terms of cost and simplicity, a metallic luster thread using a metal vapor deposition film is preferable. There is no particular restriction on the metal vapor deposition film, and any film obtained by a known manufacturing method can be used. For example, a metal layer of a metal, an alloy, or a metal compound such as gold, silver, aluminum, nickel, or tin can be formed on various films such as polyester, polyamide, and polyvinyl chloride by a known method such as vapor deposition, sputtering, ion beam, ion plating, or coating. In addition, a metallic luster of any color can be obtained by coloring. Furthermore, in order to protect the metal layer, a polymer coating or various films can be laminated. The obtained metallic luster film can be slit to form a metallic luster thread.
[0016] The width L of the metallic gloss thread in the present invention is 130 μm or less. The width L is preferably 110 μm or less, more preferably 100 μm or less. If it exceeds the above range, a fine appearance cannot be obtained, and the texture becomes hard and the touch becomes poor. The width L is 50 μm or more. It is preferably 80 μm or more. If it is less than the above range, the gloss appearance becomes poor and the quality is easily deteriorated due to fluffing, etc. The width L of the metallic gloss thread refers to the longest part in the cross section perpendicular to the fiber axis direction, and does not necessarily have to coincide with the slit width. The measurement method is as described in the examples below. The thickness of the metallic gloss thread is not particularly limited, but is generally 1 to 30 μm.
[0017] The filaments contained in the lame yarn of the present invention are not particularly limited, and natural fibers, chemical fibers, synthetic fibers, etc. can be used as appropriate, but synthetic fibers are preferred in terms of strength and cost. Examples of polymers constituting synthetic fibers include polyalkylene terephthalates such as polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, and polytrimethylene terephthalate, polyesters such as polylactic acid, polyolefins such as polypropylene, polycarbonates, polyacrylates, polyamides, polyurethanes, and polyphenylene sulfides, and mixtures of one or more of their copolymers. Among them, thermoplastic synthetic fibers using thermoplastic polymers are preferred. In terms of improving the softness of the surface touch, it is a preferred embodiment of the present invention to use a copolymer at least in part.
[0018] The strength of the filament in the present invention is 5.5 cN / dtex or more. It is preferably 6.0 cN / dtex or more. The strength of a general filament is 5.0 cN / dtex or less, but if the strength is less than the range of the present invention described above, it may be necessary to widen the width of the metallic luster thread to increase the lame thread strength, and a high-definition appearance may not be obtained, or if the width is narrowed, the strength may decrease, causing fluffing or yarn breakage during knitting and weaving. The upper limit is not particularly limited, but in terms of texture, it is preferably 10.0 cN / dtex or less, and more preferably 7.0 cN / dtex or less. The manufacturing method of the filament in the above range is not particularly limited, but an example is a manufacturing method in which a high polymerization degree polymer is used and an undrawn yarn melt-spun at a low spinning speed is subjected to multi-stage drawing using multiple heating rollers.
[0019] The total fineness of the filaments is preferably 15 dtex or less, more preferably 12 dtex or less. The total fineness in the above range is preferable in terms of obtaining a highly detailed appearance, soft texture, and smooth touch. The total fineness is preferably 5 dtex or more, more preferably 8 dtex or more. The total fineness in the above range is preferable in terms of suppressing the generation of fluff and providing a good touch.
[0020] The filament diameter D is preferably 45 μm or less, more preferably 40 μm or less. The filament diameter in the above range is preferable in terms of obtaining a highly detailed appearance, a soft texture, and a smooth feel. In addition, it is preferably 20 μm or more, more preferably 30 μm or more. The filament diameter D in the above range is preferable in terms of obtaining a good feel. The filament diameter D in the present invention is a value obtained by converting the total fineness of the filament into a monofilament having a perfect circular cross section, specifically, a value measured by the method of the examples described later. The filament in the present invention may be a multifilament or a monofilament, but the value of the diameter D is a value converted from the total fineness regardless of the number of filaments.
[0021] The cross-sectional shape of the filament when cut in a direction perpendicular to the length direction is not particularly limited, and may be either a perfect circle or an irregular cross-sectional shape. The irregular cross-sectional shape may be a flat cross-section, a polygonal cross-section such as a triangle, a rectangle, a hexagon, or an octagon, a daruma cross-section having a partially uneven portion, a Y-shaped cross-section, a star-shaped cross-section, or the like. In the present invention, an irregular cross-sectional shape is preferable from the viewpoint of gloss, and a triangular cross-section is more preferable.
[0022] In the present invention, it is preferable that the filament contains various additives such as inorganic substances such as titanium oxide, silica, barium oxide, carbon black, colorants such as dyes and pigments, flame retardants, fluorescent whitening agents, antioxidants, or ultraviolet absorbers. In the present invention, it is particularly preferable to contain titanium oxide, which gives a natural color tone to a high-definition appearance, is excellent in weather resistance and discoloration resistance, and is also preferable in terms of surface touch. The concentration of titanium oxide is preferably 0.1% by mass or more, and more preferably 0.2% by mass or more, relative to the filament containing it. When titanium oxide is contained in the above range or more, the projections on the yarn surface increase, and the touch feeling when made into a fabric is further improved. In addition, titanium oxide is preferably 15.0% by mass or less, more preferably 5.0% by mass or less, and even more preferably 3.0% by mass or less. By setting the titanium oxide concentration to the above range or less, the projections on the yarn surface can be appropriately controlled, and a soft surface touch feeling can be easily obtained. The titanium oxide concentration is a value measured by the method described in the Examples below.
[0023] The lamé yarn of the present invention includes a metallic luster yarn and a filament, but the form is not particularly limited. Examples include twisted yarn, false twisted intertwined composite, and air processing, but twisted yarn is preferred in terms of a calm appearance and smooth touch. The twisted yarn form is not particularly limited to round twist, bellows, sash, briyan, and hagoromo, but sash is preferred in terms of excellent texture with a soft surface touch and a precise, high-definition appearance that could not be obtained with conventional lamé yarns. For example, FIG. 1 shows one embodiment of a lamé yarn (3) in which a metallic luster yarn (1) and a filament (2) are twisted in a sash form. The manufacturing method is also not particularly limited, and a conventionally known method can be adopted, such as twisting a metallic luster yarn cut into a slit shape into a core thread and a filament, etc., into a sash shape.
[0024] In the lame yarn of the present invention, the ratio ((LD) / L) of the difference (LD) between the width L of the metallic luster thread and the diameter D (μm) of the filament to the width L (μm) of the metallic luster thread (hereinafter, this ratio may be referred to as the "appearance index") is 0.70 or less. If it is 0.70 or less, when it is made into a fabric, the gaps between adjacent threads will create a fine unevenness on the surface of the fabric, resulting in an elegant light luster and a highly delicate appearance. The smaller the number, the more visually delicate it is, but it is sufficient as long as it is 0.70 or less. For the above reasons, the lower limit of the appearance index is not particularly limited, but it is preferable that it is 0.50 or more in terms of ease of production. On the other hand, if the appearance index is less than the above range, a highly detailed appearance cannot be obtained, and the softness and surface touch feeling will also deteriorate. In the present invention, the range of this appearance index, as well as the range of the width L of the metallic luster thread and the strength of the filament are within the above-mentioned range of the present invention.
[0025] The total fineness of the lame yarn of the present invention is 50 dtex or less. It is preferably 45 dtex or less, and more preferably 40 dtex or less. If it exceeds the above range, it is difficult to obtain a fine appearance and the texture becomes hard. In addition, the total fineness is 10 dtex or more, preferably 20 dtex or more, and more preferably 30 dtex or more. If the total fineness is less than the above range, the glossy appearance is poor and the quality is easily reduced due to fluffing, etc.
[0026] The woven or knitted fabric of the present invention is not particularly limited as long as it contains the lame yarn of the present invention. The structure of the woven or knitted fabric is also not particularly limited, and in the case of a woven fabric, the structure may be any of a plain structure, a twill structure, a satin structure, and a variation thereof, depending on the purpose of use. In the case of a knitted fabric, the structure may be any of a plain structure, an interlock structure, a smooth structure, a half structure, a satin structure, a jacquard structure, and a variation thereof, depending on the purpose of use. The method of manufacturing these woven or knitted fabrics can be performed using a known weaving machine or knitting machine, and does not require a particularly special method. In the present invention, the woven or knitted fabric is a general term including a woven fabric, a knitted fabric, and a woven and knitted fabric. EXAMPLES
[0027] The present invention will now be described in detail with reference to examples, but the present invention is not limited thereto. The physical properties described in the text and examples were measured by the following methods.
[0028] [Total fineness of multifilament and lame yarn] The total fineness was calculated according to JIS L1013 8.3 (2010) Method A, and the value rounded to an integer according to Rule B (rounding method) of JIS Z8401 was used as the total fineness.
[0029] [Strength of multifilament] Measured in accordance with JIS L1013 8.5.1 (2010) Tensile strength.
[0030] The gripping distance was 200 mm, the pulling speed was 200 mm / min, and the load-elongation curve was obtained using a tensile tester (manufactured by Shimadzu Corporation). The load value at break was divided by the initial fineness, and this was taken as the tensile strength. In the present invention, the figures were rounded off to one decimal place.
[0031] [Titanium oxide concentration] The measurement was performed according to JIS L1013 8.26 (2010) for titanium oxide, and the average of two measurements was rounded to one decimal place according to Rule B (rounding method) of JIS Z8401 to obtain the titanium oxide concentration.
[0032] [Filament diameter D] The diameter D (μm) was calculated by converting the total fineness of the multifilaments and the density of the resin obtained above into the diameter of a perfectly circular monofilament according to the following formula. D(μm)=11.9×√((9 / 10)× Fineness(dtex)) / (ρ) In the following examples, the density p was 1.38 for polyester and 1.14 for polyamide. The density p was calculated using the value obtained by JIS K7112 (1999) Method A.
[0033] [Width of metallic gloss thread L] Using a vernier caliper with a minimum reading of 0.02 mm as specified in JIS B7507, a test yarn with a length of 300 mm was taken and measurements were taken at three points approximately equally spaced along the length. The longest width at each measurement point was measured and the average value was expressed in μm as L (μm).
[0034] Appearance Index Using the diameter D (μm) of the multifilament and the width L (μm) of the metallic luster yarn determined by the above method, the value was calculated by the following formula, rounded off to the nearest two decimal places. Appearance index=(LD) / L.
[0035] [High-definition appearance] The high-definition appearance was evaluated by visual inspection by 10 skilled persons using the following three-level judging method. ⊚ and ○ were considered to be acceptable. ◎: Precision down to the smallest details, with a strong high-definition appearance. ○: Precision down to the smallest detail, with a highly detailed appearance. ×: The details are rough and the high-definition appearance is weak.
[0036] [Texture] The softness was evaluated by 10 experts using the following four-level rating system. ⊚ and ◯ were considered to be acceptable. ◎: A texture that feels particularly soft when touched with the hand. ○: Feels soft when touched with the hand. △: Feels slightly soft when touched with the hand. ×: The texture does not feel soft when touched with the hand.
[0037] [Organization] The knitting properties were evaluated as follows: no knitting yarn breakage was observed, and x was observed.
[0038] [Example 1] A 100μm wide metallic luster yarn made by vapor-depositing silver on a polyester film was twisted with a triangular cross-section polyamide filament with 8 decitex per filament, diameter 30μm, strength 6.4cN / dtex, titanium oxide content 0.3% by mass, to obtain a lamé yarn. The obtained lamé yarn had a total fineness of 34 decitex and an appearance index of 0.70.
[0039] The obtained lame yarn was knitted into a smooth structure on a 32-gauge circular knitting machine, and the circular knitted fabric was opened and subjected to relaxation scouring (temperature 95°C), pre-setting (temperature 190°C), dyeing processing with acid dyes (temperature 95°C), and final setting (temperature 170°C). The obtained knitted fabric had a soft surface touch, excellent texture, and a highly detailed appearance with precise detail.
[0040] [Example 2] A 100μm wide metallic luster yarn made by vapor-depositing silver on a polyamide film and a triangular cross-section polyamide filament with 11 decitex and 5 filaments, a diameter of 35μm, a strength of 6.1cN / dtex, a titanium oxide content of 0.3% by mass, were twisted together to obtain a lame yarn. The obtained lame yarn had a total fineness of 37 decitex and an appearance index of 0.65.
[0041] The obtained lame yarn was knitted into a smooth structure on a 32-gauge circular knitting machine, and the circular knitted fabric was opened and subjected to relaxation scouring (temperature 95°C), pre-setting (temperature 190°C), dyeing processing with acid dyes (temperature 95°C), and final setting (temperature 170°C). The obtained knitted fabric had a soft surface touch, excellent texture, and a highly detailed appearance with precise detail.
[0042] [Example 3] A metallic luster yarn with a width of 80 μm, made by vapor-depositing silver on a polyester film, and a polyester filament with a triangular cross section, 12 decitex per filament, a diameter of 33 μm, a strength of 6.2 cN / dtex, a titanium oxide content of 0.3 mass%, were twisted together to obtain a lame yarn. The obtained lame yarn had a total fineness of 35 decitex and an appearance index of 0.58.
[0043] The obtained lame yarn was knitted into a smooth structure on a 32-gauge circular knitting machine, and the circular knitted fabric was opened and subjected to relaxation scouring (temperature 95°C), presetting (temperature 185°C), dyeing with disperse dyes (temperature 130°C), and final setting (temperature 150°C). The obtained knitted fabric had a soft surface touch, excellent texture, and a highly detailed appearance with precise detail.
[0044] [Example 4] A metallic luster yarn with a width of 80 μm, which was made by vapor-depositing silver on a polyester film, and a polyester filament with a triangular cross section and a diameter of 38 μm, a strength of 6.3 cN / dtex, and a titanium oxide content of 0.3 mass%, were twisted together to obtain a lame yarn. The obtained lame yarn had a total fineness of 39 decitex and an appearance index of 0.52.
[0045] The obtained lame yarn was knitted into a smooth structure on a 32-gauge circular knitting machine, and the circular knitted fabric was opened and subjected to relaxation scouring (temperature 95°C), presetting (temperature 185°C), dyeing with disperse dyes (temperature 130°C), and final setting (temperature 150°C). The obtained knitted fabric had a soft surface touch, excellent texture, and a highly detailed appearance with precise detail.
[0046] [Example 5] A 100μm wide metallic luster yarn made by vapor-depositing silver on a polyamide film was twisted with a polyamide filament having a circular cross section, a diameter of 35μm, a strength of 6.1cN / dtex, and a titanium oxide content of 0.3% by mass, to obtain a lamé yarn. The obtained lamé yarn had a total fineness of 37 dtex and an appearance index of 0.65.
[0047] The obtained lame yarn was knitted into a smooth structure on a 32-gauge circular knitting machine, and the circular knitted fabric was opened and subjected to relaxation scouring (temperature 95°C), pre-setting (temperature 190°C), dyeing processing with acid dyes (temperature 95°C), and final setting (temperature 170°C). The obtained knitted fabric had a soft surface touch, a texture, and a high-definition appearance.
[0048] [Example 6] A 100μm wide metallic luster yarn made by vapor-depositing silver on a polyamide film was twisted with a triangular cross-section polyamide filament of 11 decitex (5 filaments), diameter 35μm, strength 6.1cN / dtex, titanium oxide content 0 mass%, to obtain a lame yarn. The obtained lame yarn had a total fineness of 37 decitex and an appearance index of 0.65.
[0049] The obtained lame yarn was knitted into a smooth structure on a 32-gauge circular knitting machine, and the circular knitted fabric was opened and subjected to relaxation scouring (temperature 95°C), pre-setting (temperature 190°C), dyeing processing with acid dyes (temperature 95°C), and final setting (temperature 170°C). The obtained knitted fabric had a soft surface touch, a texture, and a high-definition appearance. In addition, compared to Example 5, it had a beautiful drape and an elegant, natural luster.
[0050] [Comparative Example 1] A metallic luster yarn with a width of 100 μm, made by vapor-depositing silver on a polyester film, and a polyamide filament with a triangular cross section and a diameter of 61 μm, a strength of 6.1 cN / dtex, a titanium oxide content of 0.3 mass%, were twisted together to obtain a lamé yarn. The obtained lamé yarn had a total fineness of 59 dtex and an appearance index of 0.39.
[0051] The obtained lame yarn was knitted into a smooth structure on a 32-gauge circular knitting machine, and the circular knitted fabric was opened and subjected to relaxation scouring (temperature 95°C), presetting (temperature 190°C), dyeing processing with acid dyes (temperature 95°C), and final setting (temperature 170°C). The obtained knitted fabric had a hard texture and did not have a high-definition appearance.
[0052] [Comparative Example 2] A 200μm wide metallic luster yarn made by vapor-depositing silver on a polyamide film was twisted with a triangular cross-section polyamide filament of 167dtex, 48 filaments, 124μm diameter, 4.6cN / dtex strength, 0.3% titanium oxide content, and a cross-twist to obtain a lame yarn. The obtained lame yarn had a total fineness of 176dtex and an appearance index of 0.38.
[0053] The obtained lame yarn was knitted into a smooth structure on a 32-gauge circular knitting machine, and the circular knitted fabric was opened and subjected to relaxation scouring (temperature 95°C), presetting (temperature 185°C), dyeing processing with disperse dyes (temperature 130°C), and final setting (temperature 150°C). The obtained knitted fabric had a hard texture and did not have a high-definition appearance.
[0054] [Comparative Example 3] A metallic luster yarn with a width of 100 μm, made by vapor-depositing silver on a polyester film, and a polyamide filament with a triangular cross section and a diameter of 41 μm, a strength of 5.1 cN / dtex, a titanium oxide content of 0.3 mass%, were twisted together to obtain a lamé yarn. The obtained lamé yarn had a total fineness of 38 dtex and an appearance index of 0.59.
[0055] The obtained lamé yarn was knitted into a smooth structure on a 32-gauge circular knitting machine, but yarn breakage occurred and knitting was not possible.
[0056] [Table 1] [Explanation of symbols]
[0057] 1:Metallic luster thread 2: Filament 3: Glitter thread
Claims
1. A lame yarn comprising a metallic luster yarn and a filament, wherein the width L of the metallic luster yarn is 50 μm or more and 130 μm or less, the strength of the filament is 5.5 cN / dtex or more, the total fineness of the lame yarn is 10 dtex or more and 50 dtex or less, and the ratio ((L-D) / L) of the difference (L-D) between the width L of the metallic luster yarn and the diameter D of the filament to the width L of the metallic luster yarn is 0.70 or less.
2. The lamé yarn according to claim 1, wherein the filaments are thermoplastic synthetic fibers.
3. The lame yarn according to claim 1 or 2, wherein the filaments have a non-circular cross-sectional shape.
4. The lame yarn according to claim 1 or 2, wherein the filaments contain titanium oxide.
5. The lame yarn according to claim 4, wherein the concentration of the titanium oxide is 0.1% by mass or more and 15.0% by mass or less relative to the filament.
6. A woven or knitted fabric comprising the lame yarn according to claim 1 or 2.
Citation Information
Patent Citations
In a digital electronic still camera
JP1989000868A
Composite tinsel and its production
JP1999217738A
Fine-spun twisted union yarn and fabric
JP2000054234A
Stretch lame yarn and manufacturing method thereof and fabric using the same
JP2012207343A
